Severe Airway Obstruction due to Massive Retropharyngeal Hematoma in a Warfarin-Taking Patient with a Normal International Normalized Ratio - Hyun Young Cho; Hyung Il Kim (Journal of Trauma and Injury)
Warfarin is used as part of the treatment of various diseases, and laboratory monitoring of its effects is required. Airway hematoma secondary to warfarin is rare, but can be fatal because of potential airway obstruction. Rapid definitive airway establishment is crucial if airway obstruction is suspected. This complication is more likely to occur in those with elevated coagulation laboratory values. However, we experienced a patient in whom a massive retropharyngeal hematoma caused airway obstruction after a non-severe motor vehicle collision. The patient had been taking warfarin, and had coagulation parameter values within the normal ranges. A major fracture or hemorrhage was not anticipated. Upon examination, a massive retropharyngeal hematoma was noted. Orotracheal intubation failed due to an airway obstruction. Emergency tracheostomy and an operation for hematoma removal were performed. Physicians must always consider the possibility of airway hematoma in warfarin-taking patients with normal coagulation values regardless of the severity of mechanism of injury